McDuff's Christmas - Wells, Rosemary (Hyperion Books for Children, 2005)
On Christmas Eve, McDuff's persistent "woofing" begins to annoy Fred and Lucy, but it leads to the rescue of Santa, whose sleigh has gotten stuck in the snow.